(untitled) (Confluenţe Bibliologice, 2021)
In this article the author presents the conditions included in the act of Union: provincial autonomy, preservation of local institutions, representatives in the Government and Parliament of Bucharest, personal freedom, freedom of speech and faith. The union of Bessarabia with Romania was related to the relations between the Bessarabian Church and the one from the Old Kingdom and the attitude of the authorities from Bucharest towards the convocation of the local synod in Bessarabia. In order to achieve the Union of the Churches of Bessarabia with the Romanian Orthodox Church, it was necessary to take into account the only church authority between the Prut and the Dniester, to express the opinions of the local church, at that time, was the Preparatory Commission of the synod, composed of representatives of the clergy and laity.